Curating Dissent: Indigenous Artistic Interventions as Counter-Narratives in Settler-Colonial Archives - Mary-Jane Wood; Caelin Damayanti; Dian Rahayu; Sandro Louise Oliveirra; Muhammad Hasan (Enigma Institute, 2025)
Settler-colonial archives have historically functioned as instruments of state power, perpetuating narratives that erase or marginalize Indigenous peoples' histories, knowledges, and sovereignties. This study investigated the growing phenomenon of contemporary Indigenous artistic interventions within these institutions, framing them as critical acts of